Classroom acts: New materialisms and haptic encounters in an urban classroom - Niccolini, Alyssa D; Pindyck, Maya (Reconceptualizing Educational Research Methodology, 2015)
In this piece we work with new materialist theory to experiment with the objects within a United States (US) secondary classroom in New York City (NYC). Energized by Katarina Kamprani’s (ongoing) “The Uncomfortable Project,” in which she renders everyday objects unfamiliar, we brought in unfamiliar items to a NYC classroom to change our relations to it and its relations to us. We consider how a paranoid affective relationship to ‘the urban classroom’ has limited engagement with classroom objects as lively, self-organizing, and haptically-rich with their own forms of agency and affective force. We explore a methodology of felting in which the textures of the classroom are agitated and worked to elicit surprising affects, unexpected connections, and new materialities. We see such an engagement as offering new possibilities for encountering educational spaces and as eliciting more reparative (Sedgwick, 2003) forms of theorizing and learning from urban classroom space.